The Sneetches : and other stories - Seuss, Dr. (New York : Random House, 1989)
A collection of four humorous fantasies told in rhyme.
The Sneetches -- The Zax -- Too many Daves -- What was I scared of?
Library Journal.
School Library Media Quarterly (A.A.A.L.).
Library Journal, June 2010.
School Library Media Quarterly (A.A.A.L.), May 2010.
3.5.
3.5
Keywords: Fantasy; Stories in rhyme; Stories in rhyme; Fantastic fiction